БАНКРУТСТВО ФІЗИЧНИХ ОСІБ: ПРОБЛЕМИ ТЕОРІЇ ТА ПРАКТИКИ - Butyrska, I.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
One of the main novelties of the Code of Ukraine on Bankruptcy Procedures was the introduction in Ukraine of the institution of bankruptcy of individuals, which was a long-awaited event among scientists and practitioners. It has been more than a year since the introduction of the institution of bankruptcy of individuals in Ukraine, and in some Economic Courts there are not even 10 cases of insolvency of individuals. There are many reasons for this: the high cost of the procedure, the complexity of paperwork to open proceedings, as well as a number of problematic and conflicting issues that arise in practice relevant legislative provisions. The purpose of the article is to identify problematic aspects in the legal regulation of bankruptcy of individuals and the practice of applying the relevant provisions of the Code of Ukraine on Bankruptcy Procedures, as well as to develop proposals to improve legislation in this area. Given the relatively small number of lawsuits to restore the solvency of individuals in Economic Courts, today it is necessary to state the lack of a unified approach of national commercial courts to most of the problematic issues that arise during the consideration of this category of cases. It is emphasized that since the opening of insolvency proceedings, the debtor — an individual and his family members are under the close attention of the Economic Court and the arbitral trustee, who must examine in detail all the circumstances that caused the insolvency of an individual. Based on the analysis of case law, it is established that the practice of most Economic Courts, especially Appellate, shows the absence of a legal requirement to pay court fees by the debtor for filing an application to open insolvency proceedings, and the application of requirements to the application to open proceedings insolvency of an individual of the general requirements provided for in Art. 34 of the Code of Ukraine on Bankruptcy Procedures, is inappropriate in this part. Prohibition of the debtor’s departure abroad is a measure to ensure creditors’ claims, which should not be applied automatically in all cases, but only when it is proved that the debtor intentionally acted to prevent the procedures provided for him by the Code of Ukraine on Bankruptcy Procedures. As a result of the study, the author concludes that an individual entrepreneur has a number of unjustified preferences, compared to legal entities, to initiate bankruptcy proceedings, which is not fair in terms of equality of all entities and causes unequal position of creditors of legal entities and creditors of individuals — entrepreneurs. REFERENCES1. Levshyna Ya.O. Vidpovidalnist u protseduri bankrutstva: avtoref. dys. … kand. yuryd. nauk: 12.00.04. Donetskyi yurydychnyi instytut MVS Ukrainy. Kryvyi Rih, 2020. 20 p. [in Ukrainian].2. Ukhvala Hospodarskoho sudu Kharkivskoi oblasti vid 27.04.2020 u spravi No. 922/1213/20. Yedynyi derzhavnyi reiestr sudovykh rishen. URL: https://reyestr.court.gov.ua/Review/88954194# [in Ukrainian].3. Postanova Skhidnoho apeliatsiinoho hospodarskoho sudu vid 04.02.2020 roku u spravi No. 917/2088/19. Yedynyi derzhavnyi reiestr sudovykh rishen. URL: https://reyestr.court.gov.ua/Review/87418429 [in Ukrainian].4. Radzyviliuk V., Poliakov R. Problemy zastosuvannia hospodarsko-protsesualnykh norm u protseduri bankrutstva (neplatospromozhnosti). Pravo Ukrainy. 2020. No. 7. P. 147-158. https://doi.org/10.33498/louu-2020-07-147 [in Ukrainian].5. Postanova Verkhovnoho Sudu u skladi kolehii suddiv Kasatsiinoho hospodarskoho sudu vid 24.09.2020 u spravi No. 910/2629/20. Yedynyi derzhavnyi reiestr sudovykh rishen. URL: https://reyestr.court.gov.ua/Review/91786468 [in Ukrainian].6. Zhukov S.V. Likvidatsiina protsedura bankrutstva yurydychnykh osib vidpovidno do Kodeksu Ukrainy z protsedur bankrutstva : nauk.-prakt. posib. Kyiv: Alerta, 2021. 292 p. [in Ukrainian].7. Postanova Zakhidnoho apeliatsiinoho hospodarskoho sudu vid 09.07.2020 u spravi No. 921/786/19. Yedynyi derzhavnyi reiestr sudovykh rishen. URL: https://reyestr.court.gov.ua/Review/90616276 [in Ukrainian].8. Postanova Pivnichnoho apeliatsiinoho hospodarskoho sudu vid 07.10.2020 u spravi No. 927/318/20. Yedynyi derzhavnyi reiestr sudovykh rishen. URL: https://reyestr.court.gov.ua/Review/92226567 [in Ukrainian].9. Kredytoram vazhko otrymaty informatsiiu shchodo borzhnykiv-fizychnykh osib — advokat. Zakon i biznes. 22.10.2020. URL: https://zib.com.ua/ua/145122-kreditoram_vazhko_otrimati_informaciyu_schodo_borzhnikiv_-_f.html [in Ukrainian].10. Butyrskyi A. Kontseptsiia udoskonalennia zakonodavstva pro nespromozhnist. Pravo Ukrainy. 2018. No. 6. P. 86-97. https://doi.org/10.33498/louu-2018-06-086 [in Ukrainian].11. Poliakov R. Bankrutstvo fizychnykh osib — “novyi” instytut vikom ponad 2 tysiachi rokiv. Zakon i biznes. URL: https://zib.com.ua/ua/140297-bankrutstvo_fizichnih_osib__noviy_institut_vikom_ponad_2_tis.html [in Ukrainian].